2008
DOI: 10.1186/1742-2094-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation mediated by IL-1β increases susceptibility of dopamine neurons to degeneration in an animal model of Parkinson's disease

Abstract: Background: The etiology of Parkinson's disease (PD) remains elusive despite identification of several genetic mutations. It is more likely that multiple factors converge to give rise to PD than any single cause. Here we report that inflammation can trigger degeneration of dopamine (DA) neurons in an animal model of Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
222
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(232 citation statements)
references
References 79 publications
(82 reference statements)
10
222
0
Order By: Relevance
“…Numerous studies focusing on the association between depression and degenerative diseases have used pro-inflammatory cytokine levels as the basic criterion (74,75). These models have been somewhat conclusive in providing the evidence that depression precedes degenerative diseases.…”
Section: Cytokine-associated Depressive Symptoms and Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies focusing on the association between depression and degenerative diseases have used pro-inflammatory cytokine levels as the basic criterion (74,75). These models have been somewhat conclusive in providing the evidence that depression precedes degenerative diseases.…”
Section: Cytokine-associated Depressive Symptoms and Neurodegenerationmentioning
confidence: 99%
“…These models have been somewhat conclusive in providing the evidence that depression precedes degenerative diseases. In addition, the studies indicate that degeneration is nothing but the consequence of neuroinflammation (70)(71)(72)(73)(74)(75)(76)(77)(78). In one such instance, a non-toxic dose of bacterial endotoxin that resulted in increased secretion of cytokines, as well as activation of microglia, also resulted in extended loss of dopaminergic neurons to a subsequent suboptimal inflammatory stimulus (6-hydroxydopamine).…”
Section: Cytokine-associated Depressive Symptoms and Neurodegenerationmentioning
confidence: 99%
“…As the disease progresses there is gradual circuitry degeneration within the nigrostriatal pathway, producing motor, cognitive and psychiatric symptoms (Braak et al, 2003). Despite intensive research the aetiology of this neurodegenerative disease still remains unclear with ~10% of cases with a clear genetic origin while the rest are of idiopathic origin although a number of risk factors have been identified including age, genetic predisposition, environmental toxins, neuronal injury such as traumatic brain injury (TBI) or stroke, and bacterial or viral infections (Bekris et al, 2010;Koprich et al, 2008;Tansey and Goldberg, 2010). The most significant environmental factors implicated in idiopathic PD are pesticides and have been shown to induce oxidative stress which leads to increased lipid peroxidation, DNA damage, mitochondrial dysfunction and ultimately dopaminergic neuronal dysfunction in the SNpc (Dick, 2006;Jenner, 2003).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Another group however, has demonstrated that LPS-induced increase of MCP-1, RANTES, MIP-1 , IL-8, IL-6 and IFN levels secreted by peripheral blood mononuclear cells significantly correlated with the severity of PD symptoms (Reale et al, 2009). Systemic low level of inflammation induced by a non-toxic dose of LPS has been shown to increase the severity of nigral DA neuronal cell loss in response to a subsequent low-dose of 6-OHDA in the rat model of PD (Koprich et al, 2008), while chronic systemic IL-1 also exacerbated neurodegeneration and microglial activation in the SN of 6-OHDA-treated rats (Pott Godoy et al, 2008). These data support the role of primed microglia, in the "two-hit hypothesis".…”
Section: Systemic Inflammation and Parkinson's Diseasementioning
confidence: 96%
“…Clinical and epidemiological reports suggest a correlation between systemic inflammatory events, chronic neuroinflammation and the aetiology and progressive nature of PD (Ferrari & Tarelli, 2011;Long-Smith et al, 2009;Perry, 2010). Postulated risk factors implicated in idiopathic PD include age, genetic predisposition, bacterial or viral infections, neuronal injury such as traumatic brain injury or stroke, and environmental toxins (Koprich et al, 2008;Tansey & Goldberg, 2010). Associations were first established towards the end of the first world war when the H1N1 influenza-A pandemic was coupled with a dramatic increase in post-encephalitic Parkinsonism (PEP) (also referred to as "sleeping sickness" or von Economo encephalitis) (Jang et al, 2009a;Rail et al, 1981;Tansey et al, 2007).…”
Section: Systemic Inflammation and Parkinson's Diseasementioning
confidence: 99%